Depression, anxiety, and stress among adult Diabetic patients attending diabetic clinic at Hospital Tengku Ampuan Afzan, Pahang state, Malaysia - Al-Ani, Ali Sabri Radeef; Musa, Ramli; Nik Ahmad, Nik Nur Fatnoon; Faisal, Ghasak Ghazi (2014)
Introduction: Diabetes mellitus is a serious chronic illness with an alarming increase of prevalence in Malaysia. Since diabetic patients are more prone to psychological disturbances that may affect glycemic control, quality of life, self-care and compliance with medication, it is crucial to detect depression, anxiety and stress symptoms among diabetic patients. Methodology: This is a cross sectional study conducted among 200 patients with diabetes mellitus attending the diabetic clinic at the Hospital Tengku Ampuan Afzan, Pahang state, Malaysia. The self-rating Bahasa Malaysia version of the Depression Anxiety and Stress Scales (DASS-42) was used to determine the prevalence and severity of depressive, anxiety and stress symptoms. Results: The prevalence of depression, anxiety, and stress among diabetic patients was 13.5%, 28%, 11% respectively. Most of the patients with emotional disturbances had moderate depression and anxiety symptoms. However, stress symptoms were mild. Although females showed higher prevalence of depression, anxiety and stress, only anxiety was statistically significant. Conclusion: Symptoms of depression, anxiety, and stress are evident in diabetic patients among which anxiety symptoms are the most prominent. Keywords: DASS-42, Diabetic Patients, Malaysia